2002
DOI: 10.1080/00071660120109926
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient status of crop contents of rural scavenging local chickens in Tanzania

Abstract: 1. A total of 144 chickens purchased from peasants in Morogoro, Tanzania were slaughtered, their crops dissected and the contents analysed. The birds consisted of 48 chickens from each of three climatic zones (warm and wet, warm and dry, cool and wet). Seventy-two chickens were slaughtered in each season, that is short rainy and long rainy season. 2. Cereal grains, bran, green forages, insects/worms and kitchen food wastes were the main crop contents and their composition varied significantly with season and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
24
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 4 publications
7
24
2
Order By: Relevance
“…This could indicate that the mature birds received sufficient protein. Mwalusanya et al (2002) recorded that the crop content of chickens in Tanzania contained 104 g CP/kg DM, and Mekonnen et al (2010) reported a level of 129 -150 g CP/kg in chickens in Ethiopia. In the present study the highest CP level was observed in winter, the driest season, when there is no abundance of insects and worms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could indicate that the mature birds received sufficient protein. Mwalusanya et al (2002) recorded that the crop content of chickens in Tanzania contained 104 g CP/kg DM, and Mekonnen et al (2010) reported a level of 129 -150 g CP/kg in chickens in Ethiopia. In the present study the highest CP level was observed in winter, the driest season, when there is no abundance of insects and worms.…”
Section: Discussionmentioning
confidence: 99%
“…A Ca concentration of approximately 8.8 g/kg DM for broilers and 35 g/kg DM for leghorn layers was recommended by Rama Rao et al (2003) at low dietary phosphorus levels (3.5 g and 2.8 g of non-phytin P/kg feed, respectively). It is well documented that adult laying hens tend to select feedstuffs with higher levels of Ca than other chicken classes because of their higher Ca requirements to synthesize the eggshell (Payne, 1990;Mwalusanya et al, 2002). Since about 0.50 -0.80 total P in plant feedstuffs is bound as phytate P (Steiner et al, 2007), which is poorly available to monogastric animals (Pointillart et al, 1984) it can be concluded that the chickens in this study had a low intake of P. Supplementation of Ca and P seems to be necessary to improve the nutritional status of the local chickens, which in turn should improve their productivity.…”
Section: Discussionmentioning
confidence: 99%
“…This has been reported in studies conducted in countries such as Ethiopia, Indonesia, Sri Lanka and Tanzania. 6,7,4 Although not clearly estimated, sufficient SFRB may be available to scavenging village chickens in the rainy season, but there is scarcity when it is dry, especially during the spring season when there are less crop residues and the plants are beginning to sprout. In the rainy season, insects/worms and green forage materials are in abundance whilst in the harvesting season there is a high supply of cereal grains and a low supply of green forages and insects/worms.…”
Section: Introductionmentioning
confidence: 99%
“…1 The major feed sources for village chickens are worms, insects, seeds, green leaves and other plant materials available in the backyard. 4 According to, 5 grains, bran and household food leftovers are occasional sources of supplementary feed in purely free-ranging systems. The SFRB for village chickens varies immensely with season, climate and location.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the food habits of other birds, crop or gizzard contents are analysed which give more accurate results as compared to faecal analysis, as food items in faeces are more difficult to recognize as compared to bird's crop or gizzard contents (Mwalusanya et al, 2002;Hagen et al, 2003;Lee et al, 2017). The current study, in case of Indian peafowl which is considered as endangered species, analysis of crop or gizzard contents is not possible hence faecal analysis was carried out.…”
mentioning
confidence: 99%